El Excentrico, 1968-04-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
April 5, 1968 [5 de abril de 1968]. No volume or issue number. Cover has picture of Lena Manriquez and an Easter-themed illustration. The headline reads, "Best Wishes for a Happy Easter, Lena Manriquez Income Tax Services."